Pilot study of the multifocal electroretinogram in ocular hypertension. Issue 10 (1st October 2000) - Chan, Henry H L; Brown, Brian
Abstract : AIMS: To investigate the variation of retinal function in ocular hypertension (OHT) using the multifocal electroretinogram (MERG), that can objectively assess regional retinal responses using kernel analysis. METHODS: Patients with OHT were recruited for 61 flash MERG recording. The first and second order kernel responses were analysed and compared with responses from a normal group. All the patients with OHT had full eye examinations and visual field analysis to ensure they had no ocular pathology, apart from high IOP (⩾ 22 mm Hg). RESULTS: In OHT, both the first and the second order kernel responses showed a reduction in magnitude compared with control values. The second order kernel responses showed larger relative reduction of amplitude than the first order responses. In addition, the macula showed a greater reduction in response than the periphery. CONCLUSIONS: First order and second order kernel analyses are useful for detecting changes of retinal response in OHT. The second order kernel analysis is important in measuring the inner retinal activity and is an important factor in detecting the early glaucoma case. Diminished macular response may be a useful sign in early glaucomatous changes.